Republic of Serbia : Fourth and Fifth Reviews Under the Stand-By Arrangement and Rephasing of the Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Serbia's Fourth and Fifth Reviews Under the Stand-By Arrangement and Rephasing of the Arrangement. The program is delivering good results, particularly in achieving key macroeconomic objectives. Significant fiscal tightening and efforts to address structural weaknesses have helped boost confidence and restore growth. This has been supported by a healthy credit recovery on the back of substantial monetary policy easing as inflation has been persistently low. Notwithstanding this progress, public debt remains elevated and delays continue in some structural reforms, in part owing to recent elections. Further structural reforms are required to improve the business climate and support Serbia's medium-term growth.